VERIFYING WIRE-GRID MODEL INTEGRITY WITH PROGRAM 'CHECK' - Trueman, C. W. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
A wire-grid model of a complex surface such as an aircraft consists of hundreds of "vertex" points joined by hundreds of wires or "links". A wire antenna analysis program such as NEC is used to find the currents on the wires. The formulation within NEC imposes restrictions on the geometry of the wires, which limit the length of "segments" compared to the wavelength, the radius compared to the wavelength, the ratio of the segment length to the radius, and so forth. This paper collects these limitations together into a set of "modeling guidelines". The"integrity" of a wire-grid is its ability to represent the electrical behaviour of the continuous surface that it models. An important aspect of integrity is conformance to the "modeling guidelines". Gross errors creep into complex grids: repeated wires, omitted wires, wires of zero length. More subtle errors which violate the "modeling guidelines" can lead to incorrect current distributions and misleading radiated or scattered fields form the wire-grid when solved with the NEC code. This paper describes a program called CHECK which examines an input geometry file for the NEC program for conformance to the "modeling guidelines" by each individual wire, by wires forming junctions, and by pairs which do not join but are closely spaced. CHECK tabulates "notes", "warnings" and "errors" to aid the user in assessing the degree to which the model satisfies the guidelines. CHECK systematically finds all the guideline violations in a model. CHECK produces lists of wires for display with computer graphics to show the location of each type of problem that CHECK finds. The guideline violations found by CHECK inherently suggest improvements that can be made to the wire-grid. [Vol. 5, No. 2. pp. 17-42 (1990)]